Pengaruh Promosi, Keragaman Produk, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di E-Commerce Lazada (Studi Pada: Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Hamzah Hamzah; Achmad Agus Priyono; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of promotion, product diversity and service quality on purchasing decisions in Lazada e-commerce. This research method uses quantitative methods. The population used by Students of the Faculty of Economics & Business, Islamic University of Malang, Class of 2019, was 100 respondents using a purposive sampling technique with criteria set by the researchers. Data collection method is by using a questionnaire and documentation. The data analysis technique used is multiple linear regression analysis using the IBM SPSS 16 program. The results of this study indicate that promotion, product diversity and service quality simultaneously influence purchasing decisions. Partially promotion has an effect on purchasing decisions, product diversity has partially had an effect on purchasing decisions, Service quality has partially had an effect on purchasing decisions. Keywords: Promotion, Diversity, Product, Service Quality, Purchase Decision